2012
DOI: 10.2139/ssrn.1980185
|View full text |Cite
|
Sign up to set email alerts
|

Security Transaction Taxes and Market Quality

Abstract: We examine nine changes in the New York State Security Transaction Taxes (STT) between 1932 and 1981. We find that imposing or increasing an STT results in wider bidask spreads, lower volume, and increased price impact of trades. In contrast to theories of STT imposition as a means to reduce volatility, we find no consistent relationship between the level of an STT and volatility. We examine the propensity of traders to switch trading locations to avoid the tax and find no consistent evidence that they will ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
(1 reference statement)
3
22
0
Order By: Relevance
“…The empirical evidence is somewhat mixed. While a number of papers find an increase in volatility (Baltagi et al, 2006;Hau, 2006;Pomeranets -Weaver, 2011), others find a negative relationship between an FTT and volatility (Jones -Seguin, 1997;Liu -Zhu, 2009) or no effect (Roll, 1989;Saporta -Kan, 1997).…”
Section: Effects On Volatility and Trading Volumesmentioning
confidence: 99%
“…The empirical evidence is somewhat mixed. While a number of papers find an increase in volatility (Baltagi et al, 2006;Hau, 2006;Pomeranets -Weaver, 2011), others find a negative relationship between an FTT and volatility (Jones -Seguin, 1997;Liu -Zhu, 2009) or no effect (Roll, 1989;Saporta -Kan, 1997).…”
Section: Effects On Volatility and Trading Volumesmentioning
confidence: 99%
“…There is general consensus in the empirical literature on FTT that it distorts market quality via a reduction in market volume and liquidity, an increase in market volatility and the cost of capital for firms (Amihud (1993); Umlauf (1993) (2011)). The study by Pomeranets and Weaver (2011) examines changes in market quality associated with nine modifications to the New York State Securities Transaction Tax (STT) between 1932 and 1981. They find that the New York FTT increased individual stock volatility, widened bidask spreads, increased price impact, and decreased volume on the New York Stock Exchange.…”
Section: Some Advantages and Disadvantages Of Implementing An Fttmentioning
confidence: 99%
“…There is a general consensus in the empirical literature that FTT reduces in market volume and liquidity and increases market volatility and the cost of capital (Amihud & Mendelson, 1992;Umlauf, 1993;Jones & Seguin, 1997;Baltagi et al 2006;Bloomfield et al, 2009;Pomeranets & Weaver, 2011). The study by Pomeranets & Weaver (2011) There is also the notorious example of an FTT in Sweden in 1984, which introduced a 1% tax on equity transactions in 1984, which it increased to 2% in 1986 (Umlauf, 1993).…”
Section: Financial Transactions Tax (Ftt)mentioning
confidence: 99%
“…The study by Pomeranets & Weaver (2011) There is also the notorious example of an FTT in Sweden in 1984, which introduced a 1% tax on equity transactions in 1984, which it increased to 2% in 1986 (Umlauf, 1993). He found that stock prices and turnover declined after an increase in the rate of FTT to 2% in 1986.…”
Section: Financial Transactions Tax (Ftt)mentioning
confidence: 99%